ANALISIS KEBERLANGSUNGAN USAHA PEMBENIHAN UDANG PT.SWADAYA MITRA PERKASA DI DESA LUK KECAMATAN RHEE KABUPATEN SUMBAWA TAHUN 2023 - Aprirachman, Rozzy; Merliana, Dinda (Publika Citra Media, 2024)
This research was conducted with the aim of determining the level of business sustainability of PT. Swadaya Mitra Perkasa located in Luk Village, Rhee District, Sumbawa Regency. Companies that act as shrimp seed producers already have a wide market. PT. Swadaya Mitra Perkasa has a product called